Multi-stakeholder platforms: Institutional options to achieve water security in the awash basin of Ethiopia. (September 2020) - Hailu, Reta; Tolossa, Degefa
Highlights: Multistakeholder Platforms is institutional options to seek joint solutions. Engaging multiple actors open up dialogues to boost the benefits of all actors. Platforms are hierarchal at the macro, meso, and micro levels. The institutions at the micro level are the mirror image of macro scale. Water security needs stewardship and reconciling various actors, sectors, and uses. Abstract: Securing water resources under common pool resources regime is becoming a challenge without proper collective actions. This paper explores Multi-stakeholder Platforms (MSPs) as a 'soft path' to realize water security using a case study of Awash River Basin. The data for this study were collected from various sources at multi-scale using a survey of key experts, in-depth interviews, focussed group discussions, participant observations, and document reviews. The data were systematically analysed using actors network analysis employing Ventism PLE for Windows Version 7.2, UCINET 6 for Windows, and Visualzyer 2.2 software. Moreover, descriptive statistics and content analyses were used. The result revealed that water resources involve Multi-stakeholder with various interests, priorities, sectors, and actors in the basin. Albeit, the vertical and horizontal linkages and interaction of the key actors are either loose or completely missed that affected the coordination mechanism. We argued that it is possible to negotiate the needs of all actors without endangering the water security of the others. MSPs- as an instrument to actualize collective actions- potentially realize this goal. To this end, we proposed three levels of MSPs based on the functions, mandates, and homogeneity of actors: (i) macro level, (ii) Meso level, and (iii) micro level. We believe that MSPs can be used as an institutional framework and pragmatically drive Integrated Water Resources Management in the basin. Thus, a successful platform requires reconciling various actors, sectors and uses, encouraging the water stewardship, as well as promoting Public-Private-Partnership in water resources management and development.